A One Health look into the emergence of zoonotic viruses at the human-animal-environment interface - Abdifetah Mohamed; Mahamed Abdi Wali (CABI One Health, 2023)
Abstract Emerging zoonotic viruses are a major public health concern, and they have caused the majority of human infectious disease outbreaks in recent decades. It is known that the emergence of zoonotic diseases is facilitated by human-caused environmental changes such as deforestation and changes in global climatic conditions. However, the complex interactions between these environmental elements and the contribution of each factor to the emergence and spread of zoonotic viral pathogens are not sufficiently addressed. Therefore, this article presents an overview of the available scientific knowledge on the major anthropogenic and climatic drivers of emerging zoonotic viruses, and also discusses the interconnections among human health, animal health, and ecosystem health in the context of emerging zoonotic viruses, and how the One Health approach can be implemented in reducing the health risks of emerging zoonotic viral pathogens. One Health impact statement The One Health approach has got more attention post-COVID-19 pandemic. However, there are multiple challenges in its real-world application. This paper presents a general One Health application framework that describes how a national One Health risk analysis (OHRA) system can be designed and implemented to predict, prevent, and control emerging zoonotic viral pathogens at the human-animal-environment interface.